Analisis Proses Bisnis Produksi pada PT Segar Murni Utama (MOJOTRAS) Mojokerto dengan Metode Quality Evaluation Framework (QEF) - Erni Dwi Hartini; Nanang Yudi Setiawan; Aditya Rachmadi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
PT Segar Murni Utama (MOJOTRAS) Mojokerto is a company engaged in the processing of Bottled Drinking Water (AMDK) which was founded in 2004 in the Mojokerto area, East Java. PT Segar Murni Utama (MOJOTRAS) Mojokerto is a company engaged in the processing of Bottled Drinking Water (AMDK). In mineral water production activities, the company produces several kinds of products, namely Gallon products, 1500 ml bottle products, 600 ml bottle products, 330 ml bottle products, and 240 ml cup products. In this production process there are things that need to be considered by the company, such as the achievement of activities that are not in accordance with the product sales target and there are several errors that occur during the production process. Therefore, it is necessary to conduct evaluation on the current production business process using the Quality Evaluation Framework (QEF) which aims to evaluate the quality of business processes based on facts. As well as the Raci Chart method which aims to identify the duties and responsibilities of participants or stakeholders in the company, and model them into the Business Process Model and Nation (BPMN). Business process evaluation can be used by companies to compare the business targets made with the final results of these business activities.